Initial Validation of the Mandarin Translation of the Stanford Social Dimensions Scale (SSDS). - Ge, Jiajia; Su, Xueyun; Uljarević, Mirko; Cai, Ru Ying (Journal of Autism & Developmental Disorders, 2026)
This study aimed to validate the Mandarin translation of the Stanford Social Dimensions Scale (SSDS). The initial validation sample consisted of 480 children with Autism Spectrum Disorder (ASD) (Mage = 9.35). Discriminant validity was appraised by comparing relevant SSDS scores among samples of children with ASD, typical development (TD) (N = 160, Mage = 7.16), and non-ASD but Neurodevelopmental Disorders (NDDs) (N = 170, Mage = 5.08). Confirmatory application of the Exploratory Structural Equation Modelling indicated that a five-factor model encompassing Social Motivation (SM), Social Affiliation (SA), Expressive Social Communication (ESC), Social Recognition (SR) and Unusual Approach (UA) provided adequate to excellent fit to the data in ASD group ([CFI] =.908, [TLI] =.930, [RMSEA] =.052, [SRMR] =.028). The factor loadings of most items constituting SM, SA, ESC, and SR factors were aligned with the original factor structure in the US sample, except items on the UA factor that showed lower loadings. The internal consistency was.93-.96, and test–retest reliability was.86. Discriminate validity was excellent, with the ASD group showing significantly lower scores compared to non-ASD NDDs and TD groups. Convergent and divergent validity of the SSDS was strong, as indexed by the pattern of correlations with relevant Social Responsiveness Scale, second edition (SRS-2), and Social Communication Questionnaire (SCQ) domains. This study provided preliminary validation of the Mandarin translation of the SSDS by largely replicating the original factor structure and showing evidence for strong discriminant, convergent, and divergent validity. Potential areas where further refinement and potential expansion of the SSDS are needed were identified.